The Chilbury Ladies' Choir [compact disc, unabridged] : a novel - Ryan, Jennifer (Jennifer L.) (Random House Audio, 2017)
Letters and journals reveal the struggles, affairs, deceptions, and triumphs of five members of a village choir during World War II as they band together to survive the upheavals of war and village intrigue on the English home front.